2010
DOI: 10.2105/ajph.2009.179424
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Schools, Segregated Curriculum: Effects of Within-School Segregation on Adolescent Health Behaviors and Educational Aspirations

Abstract: Objectives. We examined the extent to which within-school segregation, as measured by unevenness in the distribution of Black and White adolescents across levels of the English curriculum (advanced placement–international baccalaureate–honors, general, remedial, or no English), was associated with smoking, drinking, and educational aspirations, which previous studies found are related to school racial/ethnic composition. Methods. We analyzed data from wave 1 of the National Longitudinal Study of Adolescent He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…In terms of differences across ethnicities, we found that white British adolescents reported lower educational and occupational aspirations than other ethnic groups, while black African students reported the highest level of educational aspirations; confirming findings from previous studies (Walsemann & Bell, 2010;Hanson, 1994;Strand & Winston, 2008). Previous research in this area has also suggested that it is the ethnic population that has remained in the area of deprivation for longest that tends to find it harder to escape (McLeod 1995;Jackson et al, 2006).…”
Section: Running Head: the Aspirations Of Adolescents From Areas Of Dsupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of differences across ethnicities, we found that white British adolescents reported lower educational and occupational aspirations than other ethnic groups, while black African students reported the highest level of educational aspirations; confirming findings from previous studies (Walsemann & Bell, 2010;Hanson, 1994;Strand & Winston, 2008). Previous research in this area has also suggested that it is the ethnic population that has remained in the area of deprivation for longest that tends to find it harder to escape (McLeod 1995;Jackson et al, 2006).…”
Section: Running Head: the Aspirations Of Adolescents From Areas Of Dsupporting
confidence: 88%
“…Walsemann and Bell (2010) reported that black male students had higher predicted probabilities of high educational aspirations than white male students in certain schools and African American students have been found to report higher self-esteem than white students, but show, on average, lower academic achievement. Despite often having fewer resources to fall back on, non-white high school students were also more likely than white students to convert the resources they did have into consistently high expectations (Hanson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies examining the relationship between school racial composition and adolescent and early adult health outcomes found little evidence that predominantly white schools have a harmful impact on Asian adolescent and adult well-being (Walsemann and Bell 2011; Walsemann et al 2011). Although research suggests that Asians experience race related discrimination in predominantly white settings (Lee 2003; 2005), the protective nature of educational achievement and teacher support stemming from the acceptance of the model minority stereotype could offset the harmful effect of discrimination on health.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing number of studies have considered the effects of school segregation on health outcomes for children and young adults [34-38], no studies have focused on this association among older adults. Moreover, in a review of 39 studies on the association between segregation and health outcomes, 38 were found to have relied solely on measures of residential (rather than school) segregation [39], with the only study using school segregation having combined it into a composite with neighbourhood and church segregation [40].…”
Section: Introductionmentioning
confidence: 99%